Temporal Modalities in Arabic Logic - Rescher, N. author. aut Link
X, 50 p.
Keywords: The aim of this monograph is to expound the conceptions of temporalized modality at issue in various Arabic logical texts. I claim to have been able to make good logical sense of doctrines of which even the later Arab logicians themselves came to despair. In the process, a substantially new area of the history of logic has come into a clear view. I am indebted to Anne Cross (Mrs. Michael) Pelon and especially Mr. Bas van Fraassen for assistance in the research. Miss Dorothy Henle merits my thanks for preparing the difficult typescript for the printer and helping to see the book through the press. Also, I am grateful to the Editors of Foun dations of Language for inviting inclusion of the monograph in the Supple mentary Series of the journal. The present work is part of a series of studies of Arabic contributions to logic supported by research grants from the National Science Foundation. It affords me much pleasure to record my sincere thanks for this assistance.